Factor XIII deficiency: complete phenotypic characterization of two cases with novel causative mutations. (1st October 2013) - Katona, É.; Muszbek, L.; Devreese, K.; Kovács, K. B.; Bereczky, Z.; Jonkers, M.; Shemirani, A. H.; Mondelaers, V.; Ermens, A. A. M.
Summary Coagulation factor XIII (FXIII) exists as heterotetramer (FXIII‐A2B2) in the plasma and as dimer (FXIII‐A2) in cells. Activated FXIII mechanically stabilizes fibrin and protects it from fibrinolysis by cross‐linking fibrin chains and α2‐plasmin inhibitor to fibrin. FXIII is essential to maintaining haemostasis, and its deficiency causes severe bleeding diathesis. Due to improper laboratory practices, FXIII deficiency is considered the most under‐diagnosed bleeding disorder. The aim of this study was to demonstrate in two cases how FXIII deficiency is properly diagnosed and classified, and to compare results of laboratory analysis and clinical symptoms. FXIII activity from plasma and platelets was measured by a modified ammonia release assay, while FXIII‐A2B2, FXIII‐A and FXIII‐B antigens were determined by ELISA. The exon–intron boundaries and the promoter region of F13A1 gene were amplified by PCR and the amplified products were analysed by direct fluorescent sequencing. FXIII‐A mRNA in platelets was determined by RT‐qPCR. Two children with severe bleeding symptoms were investigated. In both cases FXIII activity and FXIII‐A antigen were undetectable in the plasma and platelet lysate. In the plasma no FXIII‐A2B2 antigen was found, while FXIII‐B antigen was >30% in both cases. Proband1 was a compound heterozygote possessing a known missense mutation (c.980G>A, p.Arg326Gln) and a novel splice–site mutation (c.1112+2T>C). Proband2 was homozygote for a novel single nucleotide deletion (c.212delA) leading to early stop codon. The discovered mutations explain the severity of clinical symptoms and the laboratory data. Methods precise in the low activity/antigen range are required to draw valid conclusion on phenotype–genotype relationship.